2016
DOI: 10.1097/md.0000000000004082
|View full text |Cite|
|
Sign up to set email alerts
|

Parecoxib prevents early postoperative cognitive dysfunction in elderly patients undergoing total knee arthroplasty

Abstract: Background:Trial design neuroinflammation and postoperative pain after surgery are increasingly reported in association with postoperative cognitive dysfunction (POCD). Parecoxib, a selective cyclooxygenase (COX)-2 inhibitor, is used for postoperative analgesia for its potent anti-inflammatory and analgesic effects. This study aimed to evaluate parecoxib's effects on POCD in elderly patients undergoing total knee arthroplasty.Methods:Around 134 elderly patients undergoing total knee arthroplasty were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 16 publications
(21 reference statements)
2
40
0
Order By: Relevance
“…Preclinical studies have indicated that an increased level of PGE2 in rodent hippocampus after surgery and those selective COX‐2 inhibitors, such as meloxicam and parecoxib, ameliorate postoperative cognitive decline . This is in concordance with clinical data that advocate that surgical trauma could upregulate PGE2 in the central nervous system and parecoxib decreases POCD incidence . However, in the central nervous system, there exist 4 distinct PGE2 receptors (EP1‐4), and the exact mechanism of PGE2 meditated development of PCOD need further exploration.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Preclinical studies have indicated that an increased level of PGE2 in rodent hippocampus after surgery and those selective COX‐2 inhibitors, such as meloxicam and parecoxib, ameliorate postoperative cognitive decline . This is in concordance with clinical data that advocate that surgical trauma could upregulate PGE2 in the central nervous system and parecoxib decreases POCD incidence . However, in the central nervous system, there exist 4 distinct PGE2 receptors (EP1‐4), and the exact mechanism of PGE2 meditated development of PCOD need further exploration.…”
Section: Introductionsupporting
confidence: 60%
“…Both preclinical and clinical studies suggest that selective COX‐2 inhibitors such as meloxicam and parecoxib, ameliorate postoperative cognitive decline . Moreover, selective COX‐2 inhibitor has been shown to improve memory function by downregulation of PGE2 levels in Alzheimer's diseases (AD) which have similar clinical symptoms of POCD, and these beneficial effects on memory do not depend on lowered levels of cytokines such as IL‐1 and TNF‐α .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of 165 patients after TKA suggested that preoperative administration of etoricoxib 120 mg orally was superior to postoperative administration of the same dose in terms of its morphine‐sparing effect during the first postoperative 48 h, without difference in the incidence of side effects. Apart from analgesia, celecoxib and parecoxib could also decrease early postoperative cognitive dysfunction incidence after TKA in elderly patients. At present, COX‐2 inhibitors are usually added to multimodal analgesia to reduce the consumption of opioids, without serious complications.…”
Section: Preoperative Analgesic Regimensmentioning
confidence: 99%
“…For example, ketamine, a phencyclidine derivative that not only antagonizes glutamate receptors but also has a profound anti-inflammatory effect, attenuates cognitive dysfunction following cardiac surgery [6,7]. Likewise, parecoxib, a cyclooxygenase-2 inhibitor with marked anti-inflammatory effects, also prevented cognitive decline following orthopedic surgery in an elderly cohort [8]. Recently, it was further described that dexamethasone, well known for reducing neuroinflammation in traumatic brain injury and those with cerebral edema, also improved cognitive outcome following surgery [9].…”
mentioning
confidence: 99%